Identifying the evolutionary building blocks of the cardiac conduction system. - Bjarke Jensen; Bastiaan J D Boukens; Alex V Postma; Quinn D Gunst; Maurice J B van den Hoff; Antoon F M Moorman; Tobias Wang; Vincent M Christoffels (PLoS ONE, 2012)
The endothermic state of mammals and birds requires high heart rates to accommodate the high rates of oxygen consumption. These high heart rates are driven by very similar conduction systems consisting of an atrioventricular node that slows the electrical impulse and a His-Purkinje system that efficiently activates the ventricular chambers. While ectothermic vertebrates have similar contraction patterns, they do not possess anatomical evidence for a conduction system. This lack amongst extant ectotherms is surprising because mammals and birds evolved independently from reptile-like ancestors. Using conserved genetic markers, we found that the conduction system design of lizard (Anolis carolinensis and A. sagrei), frog (Xenopus laevis) and zebrafish (Danio rerio) adults is strikingly similar to that of embryos of mammals (mouse Mus musculus, and man) and chicken (Gallus gallus). Thus, in ectothermic adults, the slow conducting atrioventricular canal muscle is present, no fibrous insulating plane is formed, and the spongy ventricle serves the dual purpose of conduction and contraction. Optical mapping showed base-to-apex activation of the ventricles of the ectothermic animals, similar to the activation pattern of mammalian and avian embryonic ventricles and to the His-Purkinje systems of the formed hearts. Mammalian and avian ventricles uniquely develop thick compact walls and septum and, hence, form a discrete ventricular conduction system from the embryonic spongy ventricle. Our study uncovers the evolutionary building plan of heart and indicates that the building blocks of the conduction system of adult ectothermic vertebrates and embryos of endotherms are similar.